Solutions and Green's Functions for Boundary Value Problems of Second-Order Four-Point Functional Difference Equations. (28th July 2010) - Shujie, Yang; Bao, Shi
Abstract : We consider the Green's functions and the existence of positive solutions for a second-order functional difference equation with four-point boundary conditions.